Effects of Whole Cottonseed Supplementation on Rumen Microbial Populations in Sheep Fed Grass Hay - Ismartoyo (Contemporary Research and Perspectives in Biological Science Vol. 10, 2025)
The aim of this experiment was to investigate the effects of feeding whole cottonseed (WCS) on the numbers of rumen microbes in the rumen of sheep fed grass hay (GH). During the first week of the experiment, two sheep were fed 800 g GH and 250 g concentrates, 50 g WCS, and 15 g minerals mixed. The whole cottonseed supplement was increased gradually as a substitute for GH, grass cube, and whole barley to reach level of 300 g WCS d-1 by the fourth week, and 500 g WCS d-1 by the eighth week. The results of this experiment indicated that supplementation up to 300 g d-1 did not affect the numbers of rumen bacteria and Polyplastron. However, the suplementation WCS at 500 g d-1 depressed the number of rumen fungi and protozoa. There was an indication of both the resilience of the rumen bacteria and the reductions in fungal and protozoal populations. It was concluded that the decrease in the number of rumen microbes might be due to the increase in the amounts of WCS supplement which contributed to additional dietary gossypol of 964 mg d-1 and additional dietary fat of 70 g kg-1 diet. In conclusion, supplementation WCS at 500 g d-1 for sheep fed GH resulted in partial defaunation of the rumen.